THE PREVALENCE AND DETERMINANTS OF DIARRHEA IN TODDLERS IN COASTAL AREA, NORTH BUTON REGENCY - Irman Ado; Yusuf Sabilu; Muhammad Ilyas Yusuf; Swaidatul Masluhiyah A.F.; Erwin Erwin (Universitas Muhammadiyah Magelang, 2021)
Diarrhea in children under five is still a disease with the second highest mortality rate after pneumonia. The World Health Organization (WHO) WHO recorded that around 5.6 million children under five died in 2016 and 8.8% were caused by diarrhea. The prevalence of diarrhea in Indonesia based on the results of Riskesdas (Basic Health Research) in 2018 decreased by 6.2 percent from Riskesdas in 2013 to 12.3%. Despite the decline, diarrhea remains the highest cause of under-five mortality among other diseases. This study is a quantitative descriptive study that aims to see the revalence and identify the determinants of diarrhea in children under five in coastal areas. The population and sample in this study were all data on diarrhea cases that occurred in the coastal area of ​​North Buton Regency during the observation period, from 2016 to 2020. The results showed that the prevalence of diarrhea in children under five in coastal areas was still quite high with a fluctuating pattern and Some of the determinant factors identified were environmental factors, namely clean water sources, family latrines, Waste Water Sewerage (WWS), heredity factors such as Low Birth Weight (LBW) and health service factors, namely Complete Basic Immunization (IDL). Further analysis is needed to determine the main determinants of the incidence of diarrhea in children under five in the coastal area in order to determine strategies for the prevention and control of diarrheal diseases in children under five.